Improving cold storage and processing traits in potato through targeted gene knockout - Clasen, Benjamin M; Stoddard, Thomas J; Luo, Song; Demorest, Zachary L; Li, Jin; Cedrone, Frederic; Tibebu, Redeat; Davison, Shawn; Ray, Erin E; Daulhac, Aurelie; Coffman, Andrew; Yabandith, Ann; et al. (Plant biotechnology journal, 2016)
Cold storage of potato tubers is commonly used to reduce sprouting and extend postharvest shelf life. However, cold temperature stimulates the accumulation of reducing sugars in potato tubers. Upon high‐temperature processing, these reducing sugars react with free amino acids, resulting in brown, bitter‐tasting products and elevated levels of acrylamide—a potential carcinogen. To minimize the accumulation of reducing sugars, RNA interference (RNAi) technology was used to silence the vacuolar invertase gene (VInv), which encodes a protein that breaks down sucrose to glucose and fructose. Because RNAi often results in incomplete gene silencing and requires the plant to be transgenic, here we used transcription activator‐like effector nucleases (TALENs) to knockout VInv within the commercial potato variety, Ranger Russet. We isolated 18 plants containing mutations in at least one VInv allele, and five of these plants had mutations in all VInv alleles. Tubers from full VInv‐knockout plants had undetectable levels of reducing sugars, and processed chips contained reduced levels of acrylamide and were lightly coloured. Furthermore, seven of the 18 modified plant lines appeared to contain no TALEN DNA insertions in the potato genome. These results provide a framework for using TALENs to quickly improve traits in commercially relevant autotetraploid potato lines.